ATP P2X3 receptors and neuronal sensitization - Fabbretti, Elsa (Frontiers in Cellular Neuroscience, 2013)
Increasing evidence indicates the importance of extracellular ATP in the modulation of neuronal function. In particular, fine control of ATP release and the selective and discrete ATP receptor operation are crucial elements of the crosstalk between neuronal and non-neuronal cells in the peripheral and central nervous systems. In peripheral neurons, ATP signaling gives an important contribution to neuronal sensitisation, especially that involved in neuropathic pain. Among other subtypes, P2X3 receptors expressed on sensory neurons are sensitive even to nanomolar concentrations of extracellular ATP, and therefore are important transducers of pain stimuli. P2X3 receptor function is highly sensitive to soluble factors like neuropeptides and neurotrophins, and is controlled by transduction mechanisms, protein-protein interactions and discrete membrane compartmentalization. More recent findings have demonstrated that P2X3 receptors interact with the synaptic scaffold protein CASK in a state dependent fashion, indicating that CASK plays a crucial role in the modulation of P2X3 receptor stability and efficiency. Activation of P2X3 receptors within CASK/P2X3 complex has important consequences for neuronal plasticity and possibly for the release of neuromodulators and neurotransmitters. Better understanding of the interactome machinery of P2X3 receptors and their integration with other receptors and channels on neuronal surface membranes, is proposed to be essential to unveil the process of neuronal sensitisation and related, abnormal pain signalling.